Pajak Dan Zakat: Suatu Kajian Komparatif - Ashar, Ashar (FENOMENA, 2013)
Zakat is source of revenues of state that biggest than ghanimah, jizyah, fai dan kharaf at the beginning of history of Islam.  Therefore not so surprising if there is opinion says in this modern era, zakat be created as Islamic economic back bone.  Zakat considered as a school of thought in Islam and also as a microcosm of the entire Islamic fiscal system.  Limited standpoint understanding from both are same namely give something likes money, goods or things to government or institution that be trusted to handle it. The problem that arises is if both of them are same whether people must carry out all.  Discourse it presented comparation form between zakat and tax.  Evidently there are similarities and differences both of them. So, zakat and tax must be set out in legislation not just at Al-Quran and Hadits also at Ijma and Qiyas.  Therefore all elements at society must concern on it to reach prosperity of all people.